New species of African Clytrinae (Coleoptera: Chrysomelidae). - Medvedev, Lev N. (Contributions to Entomology = Beiträge zur Entomologie, 1970)
As a result of a revision of material from Deutsches Entomologisches Institut two Clytrines from Africa were identified and are described in this paper. The holotypes are in the collection of DEI.Nomenclatural Actsgallomima Medvedev, 1970 (Melitonoma), spec. n.oranjeensis Medvedev, 1970 (Tituboea), spec. n.